Analisis Dasar Pertimbangan Hakim Praperadilan pada Perkara Penetapan Tersangka Tindak Pidana Korupsi Dana Desa: Studi Putusan Nomor 4/Pid.Pra/2022/PN.Kla - Rizki Perdana Bakri; Rinaldy Amrullah; Emilia Susanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Ensuring the preservation of human rights and the coherence of law enforcement's tasks are predicated on the pre-trial provisions of the criminal procedure legislation. As part of its mission to ensure that the criminal justice system is fair, the pretrial facility has put safeguards in place to monitor the effectiveness with which police officers carry out their tasks. All eyes are on the judge's evaluation of the law's applicability in light of pre-trial judgment 4/Pid.Pra/2022/PN.Kla. Normative and empirical theories of law are both used in this study's methodology. Primary data collected from the field and secondary data collected from various relevant legal sources are both used in this study. The study team included a law school professor, a prosecutor from the South Lampung District Prosecutor's office, and a judge from the Kalianda District Court. The court considered the following factors in rendering pretrial decision 4/Pid.Pra/2022/PN.Kla, in accordance with the study's conclusions: Instead of using the seizure reports and records that initially connected the suspect to the South Lampung District Prosecutor's Office ( Respondent) as evidence, the judgment was based on legal, social, and philosophical factors. Beyond that, the applicant was not suspected of being the subject of an official audit by the State Financial Loss Calculation Audit (PKKN). In order to establish a monetary loss to the state, the investigator must explicitly recognize a critical component that forms the foundation or risk of the inquiry. All of the applicant's pretrial requests were therefore granted by the court. The officials tasked with carrying out the pretrial decision's enforcement have finished their task. Kla is based on the multi-stage execution of criminal legislation.